Corrosion inhibition of mild steel in hydrochloric acid by some pyridine derivatives: An experimental and quantum chemical study - Ansari K.R.; Quraishi M.A.; Singh A. (My University, 2025)
The adsorption and corrosion inhibition effect of three pyridine derivatives namely 2-amino-6-methoxy-4-(4-methoxylphenyl) pyridine-3,5-dicarbonitrile (PC-1), 2-amino-6-methoxy-4-(4-methylphenyl) pyridine-3,5-dicarbonitrile (PC-2) and 2-amino-6-methoxy-4-phenylpyridine-3,5-dicarbonitrile (PC-3) on mild steel in 1M HCl was investigated using gravimetric, electrochemical impedance spectroscopy, potentiodynamic polarization techniques and quantum chemical study. PCs are mixed-type inhibitor mainly cathodic. Activation energy (Ea), equilibrium constant (Kads), free energy of adsorption (δG°ads) were calculated and discussed. The studied inhibitors (PCs) obeyed Langmuir's adsorption isotherm. Protective film of PCs on mild steel surface was investigated by using SEM and EDX. Quantum chemical parameters were carried out in the framework of the density functional theory (DFT). © 2014 The Korean Society of Industrial and Engineering Chemistry.